Reactive scattering of H2 from Cu(100): comparison of dynamics calculations based on the specific reaction parameter approach to density functional theory with experiment - Sementa, L. (2013)
We present new experimental and theoretical results for reactive scattering of dihydrogen from Cu(100). In the new experiments, the associative desorption of H2 is studied in a velocity resolved and final rovibrational state selected manner, using time-of-flight techniques in combination with resonance-enhanced multi-photon ionization laser detection. Average desorption energies and rota- tional quadrupole alignment parameters were obtained in this way for a number of (v = 0, 1) ro- tational states, v being the vibrational quantum number. Results of quantum dynamics calculations based on a potential energy surface computed with a specific reaction parameter (SRP) density func- tional, which was derived earlier for dihydrogen interacting with Cu(111), are compared with the results of the new experiments and with the results of previous molecular beam experiments on sticking of H2 and on rovibrationally elastic and inelastic scattering of H2 and D2 from Cu(100). The calculations use the Born-Oppenheimer and static surface approximations. With the functional derived semi-empirically for dihydrogen + Cu(111), a chemically accurate description is obtained of the molecular beam experiments on sticking of H2 on Cu(100), and a highly accurate descrip- tion is obtained of rovibrationally elastic and inelastic scattering of D2 from Cu(100) and of the orientational dependence of the reaction of (v = 1, j = 2 − 4) H2 on Cu(100). This suggests that a SRP density functional derived for H2 interacting with a specific low index face of a metal will yield accurate results for H2 reactively scattering from another low index face of the same metal, and that it may also yield accurate results for H2 interacting with a defected (e.g., stepped) surface of that same metal, in a system of catalytic interest. However, the description that was obtained of the average desorption energies, of rovibrationally elastic and inelastic scattering of H2 from Cu(100), and of the orientational dependence of reaction of (v = 0, j = 3 − 5, 8) H2 on Cu(100) compares less well with the available experiments. More research is needed to establish whether more accurate SRP-density functional theory dynamics results can be obtained for these observables if surface atom motion is added to the dynamical model. The experimentally and theoretically found dependence of the rotational quadrupole alignment parameter on the rotational quantum number provides evidence for rotational enhancement of reaction at low translational energies.